FC057: Incidence of Infections in the Avacopan Group Versus Prednisone Group in Anca-Associated Vasculitis, Results from the Phase 3 Advocate Study. (3rd May 2022) - George, Michael; Kronbichler, Andreas; Pagnoux, Christian; Springer, Jason; W.A. Westman, Kerstin; Yue, Huibin; Bekker, Pirow; Degoma, Emil; Jayne, David; Merkel, Peter
Abstract: BACKGROUND AND AIMS: Standard therapy for ANCA-associated vasculitis (AAV) includes glucocorticoids (GC), which are associated with increased infections. Avacopan is an orally administered selective inhibitor of the C5a receptor recently approved for treatment of AAV. The phase 3 ADVOCATE study tested daily avacopan as a substitute for a standard, scheduled, daily oral GC tapered regimen (all with standard background therapy), resulting in a 63% mean reduction in overall GC load for the avacopan group. At week 26, the avacopan group achieved a comparable remission rate to prednisone (72.3% versus 70.1%) and superior sustained remission at Week 52 (65.7% versus 54.9%; one-sided P = 0.0066) (1). The present analysis compared infections in avacopan and prednisone groups in the ADVOCATE trial. METHOD: ADVOCATE, a phase 3, randomized, double-blind, controlled trial in 330 patients, evaluated the efficacy and safety of avacopan. AAV patients (new onset or relapsing disease) were randomized to receive avacopan 30 mg twice daily, or a standard 20-week oral prednisone taper, plus matching placebos. Both groups had background therapy of either cyclophosphamide (followed by azathioprine) or rituximab, and additional GC exposure from premedication for rituximab, from taper of pre-randomization GC, and as required per investigator judgment. Patients were on blinded study drug for 52 weeks. Infections occurring from first dose of blinded study drug through day 56 after last dose were analyzed. RESULTS: Total mean GC use during the first 26 weeks of the study was 1073 mg with avacopan and 3193 mg with prednisone groups, and in the last 26 weeks, 296 and 489 mg, respectively. Infections were higher in the prednisone group than with avacopan: 291 events (prednisone) versus 233 (avacopan), with a 75.6% incidence (124/164) with prednisone versus 68.1% (113/166) with avacopan (Table 1 ). During the prednisone taper period (first 20 weeks), infection incidence was 54.9% in prednisone group versus 49.4% for avacopan, and after the first 20 weeks 52.4% in prednisone group versus 44.0% avacopan. Fewer patients in the avacopan group experienced serious AEs of infection (13.3%/25 events) versus prednisone group (15.2%/31 events); also serious opportunistic infections (3.6% versus 6.7%), life-threatening AEs of infection (0.6% versus 1.2%), and infections resulting in death (0.6% versus 1.2%) were fewer with avacopan (Table 1 ). No Neisseria meningitidis infections occurred in any patient in the trial. CONCLUSION: In the ADVOCATE trial, the mean dose of GCs from all sources was 63% lower in the avacopan group than the prednisone group (1349 versus 3655 total mg, respectively). The avacopan group had a numerically lower incidence of infections, including serious, life-threatening, fatal and serious opportunistic infections compared with the prednisone group.